Transforming Institutional Racism in Healthcare Management in Aotearoa - Came, H (Australian New Zealand Academy of Management (ANZAM), 2011)
New Zealand has had stark inequalities in health outcomes between Māori and Non-Māori for decades. I argue that, at least in part, embedded institutional racism within the administration of the healthcare system may contribute to these outcomes. Drawing on both qualitative and quantitative evidence from those targeted by racism I provide an overview of how systemic racism manifests in the realms of public health policy making and funding practices. Based on this evidence and informed by previous studies of such racism, within public sector administration, I offer suggestions for Pākehā managers in relation to transforming and preventing institutional racism.
Keywords: Healthcare management; Healthcare quality; Accountability; Health policy